Modelling the students' perception towards entrepreneurship in higher educational institution using multiple linear regression model - Nurul Afzan Abdullah; Muhammad Khairan Shazuan Jusoff; Syahirah Abdul Kadir; Nor Hazreeni Hamzah; Nur Safwati Ibrahim; Nurul Bariyah Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2021)
Entrepreneurship is neither science nor art. It is indeed a practice. Despite the increase in Malaysia's economy, people still have a low perception towards entrepreneurship. Due to the current pandemic issue, graduated students face problems of becoming unemployed after graduating. The rate of unemployment keeps rising day by day. Entrepreneurship might be one of the solutions to cater for this issue. Hence, this study is conducted to know the factors influencing students' perception towards entrepreneurship in higher education institutions. A cross-sectional study was done in UiTM Kota Bharu with a sample of 300 students selected by using stratified random sampling. The data was collected using a questionnaire form. Independent sample t-test and multiple linear regression were used for the data analysis. The independent t-test shows a difference in the mean of students' perception towards entrepreneurship between two faculties, and there is no significant difference in the mean of students' perception towards entrepreneurship among gender. Furthermore, the result of multiple linear regression shows four factors are significantly influencing the students' perception towards entrepreneurship. These factors are faculty, university's role, family background and entrepreneurial traits. However, the government's role and gender factors were insignificant in predicting students' perception towards entrepreneurship. The entrepreneurial trait factor was found to be the most important variable in predicting students' perception towards entrepreneurship.